Expression of iron-related proteins in feline and canine mammary gland reveals unexpected accumulation of iron. (17th November 2017) - Marques, O; Canadas, A; Faria, F; Oliveira, E; Amorim, I; Seixas, F; Gama, A; Lobo-da-Cunha, A; Silva, B Martins da; Porto, G; Lopes, C
Abstract: Dysregulation of cellular iron homeostasis in human breast cancer is reflected by the altered expression of regulatory proteins. The expressions of iron-related proteins in the mammary glands of cats and dogs have not been assessed. We evaluated the expressions of ferritin, ferroportin, hepcidin and transferrin receptor 1 in benign and malignant mammary gland lesions in cats and dogs. Iron deposition was detected using Perls' Prussian blue staining. We found no major differences in the expression of iron-related proteins between benign and malignant mammary gland lesions in either cats or dogs; however, these species exhibited accumulation of iron in benign lesions. Our findings provide an explanation for the absence of higher iron requirements by tumor cells in these animals. Further investigation of local iron homeostasis in cats and dogs and differences in their physiology compared to human breast cancer is required.